The influence of sport climbing on depressive disorders - Rosołowska-Żak, Sara; Sambura, Sambura; Paschke, Patrycja; Miczek, Igor; Pałuchowska, Julia; Szymkowicz, Anna (Quality in Sport, 2024)
Introduction: According to the World Health Organization (WHO), depression is the most common mental disorder, affecting a significant percentage of the adult population. The disease is associated with many negative health consequences and is one of the leading causes of disability and inability to work worldwide. Sports climbing can be a great method, complementary to psychotherapy, used to reduce the symptoms of depressive disorders. Aim of the study: The aim of our work is to review and summarize the most interesting conclusions from research on the impact of climbing as a complementary form of treatment for depressive disorders. Material and methods: We conducted a review of scientific publications published in the years 2004-2024 in English and Polish in the PubMed and Google Scholar databases. We used keywords such as "depression" and "sport climbing". Conclusions: Research shows that sport climbing can alleviate depressive symptoms, have a positive impact on emotion regulation and lead to changes in brain functioning.